Boatmen, Wastrels, and Demons: Figures of Literature. Issue 1 (April 2018) - Sawhney, Simona
Abstract : Engaging some of the questions opened by Ranjan Ghosh's and J. Hillis Miller's book Thinking Literature Across Continents (2016), this essay begins by returning to Aijaz Ahmad's earlier invocation of World Literature as a project that, like the proletariat itself, must stand in an antithetical relation to the capitalism that produced it. It asks: is there an essential link between a certain idea of literature and a figure of the world? If we try to broach this link through Derrida's enigmatic and repeated reflections on the secret – a secret 'shared' by both literature and democracy – how would we grasp Derrida's insistence on the 'Latinity' of literature? The groundlessness of reading that we confront most vividly in our encounter with fictional texts is both intensified, and in a way, clarified, by new readings and questions posed by the emergence of new reading publics. The essay contends that rather than being taught as representatives of national literatures, literary texts in 'World Literature' courses should be read as sites where serious historical and political debates are staged – debates which, while being local, are the bearers of universal significance. Such readings can only take place if World Literature strengthens its connections with the disciplines Miller calls, in the book, Social Studies. Paying particular attention to the Hindi writer Premchand's last story 'Kafan', and a brief section from the Sanskrit text the Natyashastra, it argues that struggles over representation, over the staging of minoritised figures, are integral to fiction and precede the thinking of modern democracy.